Case report: Suspected transfusion-related acute lung injury type II in a child with refractory systemic juvenile idiopathic arthritis complicated by macrophage activation syndrome - Gagro, Alenka; Tomičić, Maja; Škarić, Ivančica; Dawidowsky, Barbara (Frontiers in Pediatrics, 2024)
Introduction: Transfusion-related acute lung injury is a rare but potentially fatal complication, which may appear during or post-transfusion of blood products. Patients with macrophage activation syndrome, a serious life-threatening complication associated with systemic juvenile idiopathic arthritis, often require transfusion or administration of blood products for correction of cytopenia, coagulopathy and hypofibrinogenemia.Case Report: A 6-year-old girl with a past medical history of systemic juvenile idiopathic arthritis had the first relapse of the disease during which she developed macrophage activation syndrome. During this life-threatening complication, she received a second dose of whole blood derived filtered and irradiated platelets from a single male donor due to profound thrombocytopenia. Approximately one hour post-infusion, the patient developed progressive dyspnea, hypoxemia and bilateral pulmonary edema. She was promptly intubated and placed on mechanical ventilation for 40 hours. Clinical, laboratory and radiological findings, as well as the success of supportive ventilation therapy were highly suggestive of transfusion-related acute lung injury, a lifethreatening complication that occurs within six hours of blood component transfusion. Blood immunology showed no presence of anti-human neutrophil antigen and anti-leukocyte antigen class I and class II antibodies in the donor's or patient's plasma. This is a provisional file, not the final typeset article Conclusion: To the best of our knowledge, we report the first case of a child with systemic juvenile idiopathic arthritis complicated with macrophage activation syndrome who developed type II transfusion-related acute lung injury following platelet transfusion. It is important to consider transfusion-related acute lung injury in transfusion settings in these children and apply critical and restrictive approach for platelet transfusion.